2016
DOI: 10.4137/imi.s40035
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in Egyptian Systemic Lupus Erythematosus Patients: How Prevalent and Does it Impact Disease Activity?

Abstract: BACKGROUNDThe emerging role of vitamin D in immunology and autoimmune disorders has been a worldwide interest in the last decade. Systemic lupus erythematosus (SLE) patients are particularly at a delicate position predisposing them to suffer from vitamin D deficiency due to the multiple risk factors accompanying the disease. Whether vitamin D deficiency is also involved as a risk factor for developing SLE and affecting its course is a considerable concern.OBJECTIVESThe objective of this study was to estimate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
34
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 44 publications
(61 reference statements)
12
34
3
Order By: Relevance
“…Vitamin D status is related to many types of health outcomes among the elderly population and can contribute to musculoskeletal complications (including proximal myopathy, bone and muscle pain, secondary hyperparathyroidism, osteoporosis, and osteomalacia) [1], chronic diseases (cancer and cardiovascular diseases) [2], autoimmune diseases (systemic lupus erythematosus, multiple sclerosis, scleroderma or systemic sclerosis, autoimmune thyroid diseases, rheumatoid arthritis and primary biliary cirrhosis) [3, 4], and psychotic disorders (depression, self-neglect and cognitive impairment) [57]. All these diseases can cause disability among the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D status is related to many types of health outcomes among the elderly population and can contribute to musculoskeletal complications (including proximal myopathy, bone and muscle pain, secondary hyperparathyroidism, osteoporosis, and osteomalacia) [1], chronic diseases (cancer and cardiovascular diseases) [2], autoimmune diseases (systemic lupus erythematosus, multiple sclerosis, scleroderma or systemic sclerosis, autoimmune thyroid diseases, rheumatoid arthritis and primary biliary cirrhosis) [3, 4], and psychotic disorders (depression, self-neglect and cognitive impairment) [57]. All these diseases can cause disability among the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, 19 studies were included in our meta‐analysis (Figure ). Sixteen studies compared circulating 25(OH)D levels between SLE patients and healthy controls (Table ); seven Studies provided the information about the deficiency, insufficiency, sufficiency of vitamin D in both SLE patients and healthy controls (Table ); 6 studies explored the correlations between disease activity of SLE and 25(OH)D levels (Table ). The NOS scores of included studies ranged from 6 to 8 stars, indicating each of the studies had high methodological quality (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen articles with 17 individual studies reported the circulating 25(OH)D levels of 1434 SLE patients and 1533 healthy controls. Compared with healthy controls, SLE patients had significantly lower 25(OH)D levels (pooled SMD = −1.63, 95% CI: −2.51 to −0.76), and significant heterogeneity was identified among these studies ( I 2 = 98.9%, P < .001) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, a number of larger-scale case-control studies confirmed the relationship between hypovitaminosis D and the prevalence of SLE [75,76,77,78], particularly in patients with lupus nephritis [75]. In our recent age- and gender-matched case-control study of 61 SLE patients and 61 healthy controls, we found that a deficiency of the total 25(OH)D 3 level, as measured by liquid chromatography-tandem mass spectrometry, was significantly more prevalent in the patient group (19.7% vs. 3.3%, p = 0.003) [79].…”
Section: Hypovitaminosis D and Its Impact On Disease Activity And mentioning
confidence: 99%